Dielectric Spectroscopy as a Tool to Distinguish Starch and Flour - Prem Pankaj; Prabhdeep Kaur; Kuldip Singh Mann (Recent Progress in Science and Technology Vol. 6, 2023)
The present chapter aims to determine whether dielectric spectroscopy can be used to distinguish starch and flour. It is a powerful experimental tool that allows real-time, in-line measurement with simple calibration. It is successfully used in food industry, agriculture, polymer science, human health, medicine, textile etc. Particle size analysis done by sieve method indicate that corn flour do not have sigmoidal profile. Both for flour and starch samples, the dielectric properties values increase abruptly for 50oC and above. It was observed that dielectric constant of both starch and corn decreases in selected frequency range however corn starch have higher values. Dielectric spectroscopy may serve as a fast and reliable tool for distinguishing and detecting these two, thereby avoiding quality concerns or any potential misapplication of one in place of the other in the food industry.